The Mediating Role of Metacognitive Awareness in the Relationship Between Teaching Practice and Early Teacher Identity - Noorbaiti, Rahmita; Hidayanto, Taufiq (Vidya Karya, 2026)
Teacher professional identity plays a crucial role in supporting the realization of quality learning. Furthermore, the early teacher identity formed during pre-service teacher education and early career tends to persist throughout a teacher's career. However, the identification of factors shaping teacher identity and the direction of their correlations has not been extensively conducted in Indonesia, particularly concerning pre-service teacher education. Among the factors theoretically influential are metacognitive awareness and teaching practice experience. This study aims to determine the role of the mediating variable, metacognitive awareness, in influencing the relationship between students' experiences from teaching practice activities in schools and the formation of their early identity as teachers. This research is quantitative and employs a relational screening model. The instruments used are questionnaires for related variables adapted from relevant research, then translated and validated by various experts. Subsequently, correlation analysis will be conducted on the data from the three variables to determine the significance and direction of the correlation, with metacognitive awareness as the mediating variable. The results show an indirect effect of 0.344, which is greater than the direct effect of 0.131, meaning that metacognitive awareness has a significant mediating role in the relationship between teaching practice experience and early teacher identity. The implication of this research is the need for teaching practice activity designs that can facilitate pre-service teachers in developing their metacognitive awareness to achieve quality learning processes.